Design and Sustainability Aspects of Geogrid-Reinforced Flexible Pavements—An Indian Perspective - Goud, G. Narendra; Mouli, S. Sasanka; Umashankar, Balunaini; Sireesh, Saride; Madhira, R. Madhav (Frontiers in Built Environment, 2020)
Design of flexible pavements is not straightforward when reinforcement materials, such as geogrid, geocell, and other types of geosynthetic materials, are used in pavement construction. Presently in India, elasticity theory is used to analyze strains due to wheel load applied on multi-layered soil system through a pavement analysis program, IITPAVE, to design the unreinforced pavement section as per Indian Roads Congress guidelines (IRC-37: 2012). The improvement in the performance of geogrid- reinforced pavement with respect to unreinforced pavement can be quantified in terms of Layer Coefficient Ratio (LCR) or Traffic Benefit Ratio (TBR). In the present study, both LCR and TBR based approaches are proposed to design geogrid-reinforced base courses of pavements with specific goals. These specified goals included designs based on (a) reduction in consumption of aggregates, and (b) reduction in the overall cost of construction of pavement reinforced with geogrids. Design charts are provided based on LCR and TBR values corresponding to selected traffic and California Bearing Ratio (CBR) of subgrades. The benefits of reinforcement in the pavement structure are found to be high when used over weak subgrades (CBR < 5%). For example, a reduction in thickness of aggregate layer is found to be in the range of 28% to 45%. Additionally, the sustainability of geogrid-reinforced pavement is quantified by comparing the embodied carbon (EC) generated from construction of geogrid-reinforced and unreinforced pavements. EC of reinforced pavements is found to have reduced by as much as 58 to 85 tCO2e/km in comparison with unreinforced pavement.